The effect of trait mindfulness on social media rumination: Upward social comparison as a moderated mediator - Gu, Chenyu; Liu, Shiyu; Chen, Subai (Frontiers in Psychology, 2022)
Social media rumination means that social media users are inclined to worry about their posts, relevant situational elements, and ramifications of the posts on a regular basis, and it is one of the main reasons why people's use of social media is linked to unfavorable mental health and interpersonal results. Rumination is antagonistic to mindfulness, which entails paying attention on purpose and without judgment, and mindfulness appears to be useful in reducing rumination. However, in the context of social media, the nature of the relationship between rumination and mindfulness has gained less attention. The current research study indicates that trait mindfulness, upward social comparison (USC), and self-esteem are implicated in social media rumination (SMR). However, no research study has synthesized the findings into one model. Therefore, the current research study aims to explore the relationship between trait mindfulness and SMR, the mediating effect of USC, and the moderating effect of self-esteem. The model was tested using AMOS and the PROCESS macro in SPSS with bootstrapping. According to the findings, SC appears to have a moderated mediator effect on the relationship between trait mindfulness and SMR. Specifically, individuals with high mindfulness trait do not necessarily have less USC. Self-esteem moderated the above mediation. The beneficial effect of trait mindfulness on social media rumination is explained in depth in this study.